The Visual Memory of Protest - Rigney, Ann; Smits, Thomas (Protest and social movements.)
Social movements are not only remembered in personal experience, but also through cultural carriers that shape how later movements see themselves and are seen by others. The present collection zooms in on the role of photography in this memory-activism nexus. How do iconographic conventions shape images of protest? Why do some images keep movements in the public eye, while others are quickly forgotten? What role do images play in linking different protests, movements, and generations of activists? Have the affordances of digital media made it easier for activists to use images in their memory politics, or has the digital production and massive online exchange of images made it harder to identify and remember a movement via a single powerful image? Bringing together experts in visual culture, cultural memory, social movements, and digital humanities, this collection presents new empirical, theoretical, and methodological insights into the visual memory of protest.